2006
DOI: 10.1007/s10803-006-0117-y
|View full text |Cite
|
Sign up to set email alerts
|

A New Neurobehavioral Model of Autism in Mice: Pre- and Postnatal Exposure to Sodium Valproate

Abstract: Autism symptoms, including impairments in language development, social interactions, and motor skills, have been difficult to model in rodents. Since children exposed in utero to sodium valproate (VPA) demonstrate behavioral and neuroanatomical abnormalities similar to those seen in autism, the neurodevelopmental effects of this antiepileptic agent were examined in mice following its pre- or postnatal administration. Exposed pups were evaluated in a battery of neurodevelopmental procedures designed to assess V… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

13
176
0
2

Year Published

2007
2007
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 241 publications
(191 citation statements)
references
References 53 publications
13
176
0
2
Order By: Relevance
“…Several case studies (Christianson et al, 1994;Williams and Hersh, 1997;Williams et al, 2001), as well as a population study (Moore et al, 2000), reported a link between the administration of the anticonvulsant drug VPA during pregnancy and the risk of giving birth to an autistic child. Although several rodent studies explored and established the teratogenic effects of prolonged VPA administration during pregnancy in general (Vorhees 1987a, b) and in the context of autism (Narita et al, 2002;Wagner et al, 2006), we chose the VPA rat model of autism proposed by Rodier et al (1996). This model focuses specifically at the time of neural tube closure on gestational day 12.5, which is believed to be a particularly vulnerable time point for insults that may produce autistic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Several case studies (Christianson et al, 1994;Williams and Hersh, 1997;Williams et al, 2001), as well as a population study (Moore et al, 2000), reported a link between the administration of the anticonvulsant drug VPA during pregnancy and the risk of giving birth to an autistic child. Although several rodent studies explored and established the teratogenic effects of prolonged VPA administration during pregnancy in general (Vorhees 1987a, b) and in the context of autism (Narita et al, 2002;Wagner et al, 2006), we chose the VPA rat model of autism proposed by Rodier et al (1996). This model focuses specifically at the time of neural tube closure on gestational day 12.5, which is believed to be a particularly vulnerable time point for insults that may produce autistic symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…[31][32][33] Wagner and colleagues 34,35 investigated abnormalities in neonatal and juvenile mice relevant to neurodevelopmental disorders using sets of behavioral tasks for sensorimotor abilities, learning and memory, and other functional domains. The researchers utilized a test for juvenile play to reveal reduced social interaction in a genetic model for autism, the Engrailed 2 null mouse.…”
Section: Behavioral Phenotyping Of Mouse Modelsmentioning
confidence: 99%
“…253 In mice, exposure to valproic acid while in utero leads to behavioral retardation and regression during neonatal and juvenile development. 35 One hypothesis for the mechanism of teratogenic action for valproic acid is through effects on the expression of Hox (homeobox) genes. 232,254 These genes encode transcription factors that are important in regulating early development.…”
Section: Mouse Models Of Environmental Contributions To Autism Etiologymentioning
confidence: 99%
“…Inbred mouse strains, transgenic mouse models and mice with prior teratogen exposure exhibit varying degrees of face and construct validity for one or more of the core deficits observed in ASD (Wagner et al, 2006;Silverman et al, 2010;Peça et al, 2011). Given that genomic variants likely account for 0.5-2% of total ASD cases (Pinto et al, 2010), we were interested to complement existing studies on animal models by determining the extent to which an environmental risk factor might provide face and construct validity.…”
Section: Introductionmentioning
confidence: 99%